CSF concentrations of 5-methyltetrahydrofolate in a cohort of young children with autism. (14th June 2016) - Shoffner, John; Trommer, Barbara; Thurm, Audrey; Farmer, Cristan; Langley, William A.; Soskey, Laura; Rodriguez, Aldeboran N.; D'Souza, Precilla; Spence, Sarah J.; Hyland, Keith; Swedo, Susan E.
Abstract : Objective: To examine the association between cerebral folate deficiency and autism, this study examined CSF 5-methyltetrahydrofolate (5-MTHF) concentrations in a group of young children with autism, investigated the natural variation in CSF 5-MTHF over time, and assessed the relationship between CSF 5-MTHF and symptoms. Methods: CSF was collected from 67 children with a diagnosis of DSM-IV-TR autistic disorder (age, mean ± SD 43 ± 11 months), with a second CSF sample obtained 1–3 years later on 31 of these subjects (time to follow-up, 30 ± 8 months). Results: At time 1, 7% (5/67) of participants had 5-MTHF <40 nmol/L. At follow-up, 23% (7/31) of participants had 5-MTHF <40 nmol/L (only one of whom had been low at time 1). A moderate correlation with a very wide confidence interval (CI) was observed between time 1 and time 2 CSF 5-MTHF measurements (Pearson r [ p ] = 0.38 [0.04]; 95% CI 0.02–0.64). Neither the CSF 5-MTHF levels nor changes over time correlated with the clinical features of autism. Conclusions: CSF 5-MTHF levels vary significantly over time in an unpredictable fashion and do not show a significant relationship to typical clinical features of autism. Reduced CSF 5-MTHF levels are a nonspecific finding in autism. Our data do not support the use of lumbar puncture for assessment of CSF 5-MTHF in autism.